PENGEMBANGAN WISATA HIU PAUS BERBASIS IOT (INTERNET OF THINGS) MELALUI SIARAN LANGSUNG JELAJAH VIRTUAL HIU PAUS DI ALAM LIAR DI PANTAI DESA BOTUBARANI, KABILA BONE, BONE BOLANGO, GORONTALO - Himawan, Mahardika Rizqi; Tilahunga, Sukirman Dj; Hidayati, Eni; Nurliah; Amar, Fahri; Tania, Casandra (Jurnal Pengabdian Perikanan Indonesia, 2022)
The whale shark (Rhincodon typus) is the largest fish species in the world that is not aggressive to humans, so it has become a popular tourist icon. The presence of whale sharks has become a tourist magnet and has transformed Botubarani Village from an ordinary fishing village into a bustling tourist village. However, the Covid19 pandemic has dealt a severe blow to whale shark tourism on the coast of Botubarani Village. The drastic reduction in tourists not only eliminates tourist income but also stops whale shark monitoring activities. The government's New Normal pilot is the hope for the return of whale shark tourism on the coast of Botubarani Village. Preparations for the opening of PPKM in the area of ​​origin of tourists and the ease of domestic/foreign travel will be greeted with an increase in the quality and innovation of whale shark tourism at Botubarani Beach. In addition, the adaptation of tourism during the pandemic by utilizing the internet is quite promising so that tourism will stay alive. The Innovation Village of Botubarani develops a live broadcast of an underwater virtual cruise with whale shark objects periodically in the wild. This development is the first in Indonesia because it has never been done before. The use of underwater closed circuit television (CCTV) that can be accessed on land and integrated with the internet allows whale sharks on Botubarani Beach to be enjoyed by anyone and anywhere. Villages and communities on Botubarani Beach can receive input from ongoing tourism developments from tourists who come or virtually. Tourists may also be interested in coming after watching a live broadcast of whale sharks on the beach of Botubarani Village. In addition, live video recording of whale sharks can also be utilized by intellectuals, government and industry as part of the triple helix collaboration.